2019
DOI: 10.2147/idr.s206642
|View full text |Cite
|
Sign up to set email alerts
|

<p>On-treatment improvement of an emerging psychosomatic depressive disorder among salmonella carriers: a multicenter experience from Egypt</p>

Abstract: BackgroundAs physicians in a referral hospital, we observed the association between history of enteric fever and somatic disorders associated with low mood. At the Al-Hussein University Hospital, Cairo and the National Liver Institute Hospital, Menoufia, we receive patients from all over Egypt, including rural areas where enteric fever is endemic.AimHere in, 60 Egyptian patients referred to us for evaluation of different somatic disorders are reported.MethodsAfter extensive evaluations, the patients’ symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The high serum level of IL-6 had a predictive function in the pathogenesis of insulin resistance and cardiac complications in patients with diabetes. [26][27][28][29][30][31] Also, Cheng et al 32 found that increased plasma concentrations of resistin were strongly associated with subsequent development of heart failure. The association of resistin with heart failure persisted after adjustment for established heart failure risk factors, obesity, markers of insulin resistance and inflammation, and concentrations of NT-proBNP, and after exclusion of prevalent and incident CHD.…”
Section: Discussionmentioning
confidence: 99%
“…The high serum level of IL-6 had a predictive function in the pathogenesis of insulin resistance and cardiac complications in patients with diabetes. [26][27][28][29][30][31] Also, Cheng et al 32 found that increased plasma concentrations of resistin were strongly associated with subsequent development of heart failure. The association of resistin with heart failure persisted after adjustment for established heart failure risk factors, obesity, markers of insulin resistance and inflammation, and concentrations of NT-proBNP, and after exclusion of prevalent and incident CHD.…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports have suggested a possible causal association between enteric (typhoid) fever and both BD and MDD [ 77 , 78 , 79 ]. A recent study from Egypt extended these findings by documenting MDD in asymptomatic carriers of Salmonella typhi , which improved after antibiotic therapy without a need for concurrent antidepressant medication [ 80 ]. In addition, a study of psychiatric inpatients from Ethiopia found evidence of intestinal parasitic infections in 15% of patients with MDD and 9% of patients with BD [ 81 ].…”
Section: Introductionmentioning
confidence: 99%